2012
DOI: 10.1029/2010wr010088
|View full text |Cite
|
Sign up to set email alerts
|

Dominant controls on pesticide transport from tile to catchment scale: Lessons from a minimalist model

Abstract: [1] This paper proposes a minimalist modeling approach for characterizing pesticide concentrations in runoff from agricultural catchments across spatial scales. The model proposed is of an intermediate level of complexity between traditional chromatographic separation models and the more complex dual-domain models. Parsimony in the model is achieved by assuming stationarity of catchment travel time distributions and by coupling a dual-domain source zone model that describes near-surface pesticide dynamics with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Eighty-five percent of the watershed area is in eastern Vermilion County, 13 % of the watershed is in Champaign County, and 2 % of the watershed is in Edgar County. The LVR watershed consists of flat topography, with elevations ranging from 235 m in the headwaters to 174 m at the watershed outlet and with an average slope reaching at most 1 % (Zanardo et al, 2012). The long-term (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) average annual precipitation for the watershed is 990 mm yr −1 (Kalita et al, 2006).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…Eighty-five percent of the watershed area is in eastern Vermilion County, 13 % of the watershed is in Champaign County, and 2 % of the watershed is in Edgar County. The LVR watershed consists of flat topography, with elevations ranging from 235 m in the headwaters to 174 m at the watershed outlet and with an average slope reaching at most 1 % (Zanardo et al, 2012). The long-term (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) average annual precipitation for the watershed is 990 mm yr −1 (Kalita et al, 2006).…”
Section: Study Areamentioning
confidence: 99%
“…Ninety percent of the LVR watershed is agricultural land used for corn and soybean production, and the remainder consists of grassland, forest land, roadways, and farmsteads (Kalita et al, 2006). Annual area planted with soy- (Zanardo et al, 2012;Keefer, 2003), and the dominant hydrologic soil groups are B and C. The LVR watershed is a typical tile-drained watershed in Illinois. Water quantity and quality data for this watershed are available from a long-term (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003) monitoring project through which data were collected from several subsurface stations, surface stations, river stations and wetland sites in the watershed (Mitchell et al, 2003;Kalita et al, 2006).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…This irrigation 421 paddock runoff (and associated pesticide losses) is transported through a network of drains 422 which ultimately discharge into Barratta Creek introducing flow into a normally ephemeral 423 system and explains why pesticide concentrations in Barratta Creek increase prior to the 424 onset of wet season rains [17][18][19] . Several studies have shown that the dominant mechanism 425 driving the amount of pesticide lost from croplands relates to surface runoff following 426 rainfall as well as the timing of pesticide application [52][53] . In contrast, the design of the water 427 supply and discharge network of the Burdekin Water Supply Scheme means that irrigation 428 runoff within the Barratta Creek catchment drives the prolonged and elevated pesticide 429 ecological threshold values 40 for freshwater (Table 4) and/or estuarine systems (Table 5).…”
mentioning
confidence: 99%